Demographic Trends, the Dividend-Price Ratio, and the Predictability of Long-Run Stock Market Returns - Favero, Carlo A.; Gozluklu, Arie E.; Tamoni, Andrea (Journal of Financial and Quantitative Analysis, 2011)
Abstract This paper documents the existence of a slowly evolving trend in the log dividend-price ratio, DP t , determined by a demographic variable, MY t : the middle-aged to young ratio. Deviations of DP t from this long-run component explain transitory but persistent fluctuations in stock market returns. The relation between MY t and DP t is a prediction of an overlapping generation model. The joint significance of MY and DP t in long-horizon forecasting regressions for market returns explains the mixed evidence on the ability of DP t to predict stock returns and provide a model-based interpretation of statistical corrections for breaks in the mean of this financial ratio.